Microvascular and macrovascular disease and risk for major peripheral arterial disease in patients with type 2 diabetes - Woodward, M; Mohammedi, K; Hirakawa, Y; Zoungas, S; Williams, B; Lisheng, L; Rodgers, A; Mancia, G; Neal, B; Harrap, S; Marre, M; Chalmers, J (American Diabetes Association, 2016)
Objective Peripheral arterial disease (PAD) is a common manifestation of atherosclerosis in type 2 diabetes, but the relationship between other vascular diseases and PAD has been poorly investigated. We sought to examine the impact of previous microvascular and macrovascular disease on the risk of major PAD in these patients. Research Design and Methods We analysed 10624 patients with type 2 diabetes, free from baseline major PAD, in the Action in Diabetes and Vascular Disease: PreterAx and DiamicroN Modified-Release Controlled Evaluation (ADVANCE) clinical trial. The primary composite outcome was major PAD, defined as PAD-induced death, peripheral revascularisation, lower-limb amputation or chronic ulceration. The secondary endpoints were the PAD components considered separately. Results Major PAD occurred in 620 (5.8%) participants during 5 years of follow-up. Baseline microvascular and macrovascular disease were both associated with subsequent risk of major PAD after adjustment for age, sex, region of origin and randomized treatments. However, only microvascular disease remained significantly associated with PAD after further adjustment for established risk factors. The highest risk was observed in participants with history of macroalbuminuria (HR 1.91 95%CI 1.38-2.64, p<0.0001), and retinal photocoagulation therapy (1.60 [1.11-2.32], p=0.01). Baseline microvascular disease was also associated with higher risk of chronic lower-limb ulceration (2.07 [1.56-2.75], p<0.0001) and amputation (1.59 [1.15-2.22], p=0.006), while baseline macrovascular disease was associated with a higher rate of angioplasty procedures (1.75 [1.13-2.73], p=0.01). Conclusions Microvascular disease, particulary macroalbuminuria and retinal photocoagulation therapy, was strongy predictive for major PAD in patients with type 2 diabetes, but macrovscular disease was not.